Effect of Fluoride Varnish in Dental Caries: A Review - Rupsita Sahu1 , Ramesh Nagarajappa2 , Debashruti Naik3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Dental caries remains amongst the most common oral health problem affecting people in the developingcountries. The use of fluoride ions in the form of gels, foams, and varnishes are effective in preventing caries.The varnishes have been routinely used in the western European and Scandinavian countries in the last 30years because of its ability to provide an increased contact time between enamel surface and fluoride, thusinhibiting demineralization of enamel. The technique of fluoride application, along with its advantages,disadvantages, indications, contraindications, and side effects have been discussed in this review.